General geology and geoheritage potential of Rammang-Rammang, Maros, South Sulawesi, Indonesia. - Sahadariah Bakri (2017)
The Karst Maros landscape is very natural and unique which contains high level of geological diversity (geodiversity) such as rock, fossil, minerals, soil, landform and the processes that have shaped all these features over the time either on the Earth’s surface or beneath the Earth’s surface. Geoheritage is used to describe features of geodiversity which hold special meaning to people, communities or cultural group. The study area is located at Kecamatan Rammang Rammang, Kabupaten Maros of the South Sulawesi province in Indonesia. The coordinate is 04o 54’ 30” S to 04o 57’ 0” S and 119o 35’ 30” E to 119o 37’ 30” E. This research study about the Karst Maros region in Southern Sulawesi, Indonesia, about the geological heritage (geoheritage) potential of the unique landscape of the Karst Maros. This study conducted to update the geological map of study area in scale 1: 25,000 and also to identify the geoheritage potential of the study area. The lithology of this area mostly cover the limestone unit which is include in the Tonasa formation that has age from Eocene to middle Miocene. In order to achieve the objective a few methods used which are geological mapping for the update the map and the geoheritage mapping to identify the geoheritage potential of the study area. The study is more related with the scientific, social and culture aspect of the geoheritage site for direct benefits for the geodiversity conservation. All the element of geoheritage included in this research. In order to preserve and conserved this area a few threats is identify like quarrying activity near the study area which can cause the view of the rare landscape change time by time. This activity needs to be overcome in order to make the Karst Maros as a World’s Heritage.